Design and validation of an integrated meta-instrument for nursing assessment in home hospitalization: A study protocol - Paula Barrué-García; Irene Llagostera-Reverter; Águeda Cervera-Gasch; Aurora Esteve-Clavero; María Jesús Valero-Chillerón; Víctor Ortiz-Mallasén; Marta Aquilué-Ballarín; David Luna-Aleixos; María Sánchez-Galán; Víctor M. González Chordá (PLoS ONE, 2026)
Background Hospital-at-home (HaH) programs provide an effective and safe alternative to conventional hospitalization, particularly for patients with multimorbidity or complex chronic conditions. In this setting, nursing assessment plays a key role, given the intermittent nature of care and the limited presence of other professionals. However, nursing documentation in HaH remains challenging because of organizational heterogeneity, fragmented records, and the coexistence of multiple assessment tools that create redundancy and compromise information quality. The overall objective of this study is to develop and validate a meta-instrument (VALENF-HAD) that integrates the assessment of functional capacity, pressure injury risk, fall risk, frailty, nutritional status, and sleep quality in patients admitted to hospital-at-home units on the basis of the analysis of other validated measurement instruments used in nursing assessment. Methods A multicentre, cross-sectional study will be conducted in four public hospitals in Castellón Province, Spain. Participants will include adults (≥18 years) admitted to HaH units. Sociodemographic and care-related variables, along with risk-related variables, will be collected using the following instruments: functional capacity (Barthel Index and Lawton & Brody Scale), risk of pressure injuries (Braden Scale), risk of falls (STRATIFY Scale), frailty (FRAIL questionnaire), nutritional status (Nutritional Screening Initiative tool), and sleep quality (Athens Insomnia Scale). The development process of the meta-instrument consists of four phases: (I) analysis of instruments, constructs, and items; (II) meta-instrument design; (III) initial validation; and (IV) determination of clinimetric properties. Discussion This study is expected to produce a parsimonious and specific meta-instrument for hospital-at-home settings that is capable of integrating functional, nutritional, sleep, fall risk, frailty, and pressure injury assessments. Its implementation will enhance the quality and standardization of nursing documentation, reduce administrative workload, facilitate early risk detection, and free up time for direct patient care. Ultimately, this study will contribute to advancing evidence-based nursing practices in home hospitalization.